Ethnobotany of traditional medicinal plants and associated indigenous knowledge in Dawuro Zone of Southwestern Ethiopia - Mathewos Agize; Zemede Asfaw; Sileshi Nemomissa; Tizazu Gebre (BMC, 2022)
Abstract Background The study aimed at documenting the indigenous and local knowledge and use of traditional medicinal plants for treating human and livestock ailments in Dawuro Zone of Ethiopia. Methods A survey was conducted among traditional healers and native administrators through discussion, interviews, and field observations. The snowball sampling technique was used to select 384 traditional healers in purposefully selected 50 villages spanning seven districts for face-to-face individual interviews. The chi-square test was applied to establish associations between traditional healers' demographics, the distance between the village site and the nearest natural forest and a health center, and SPSS V.20 software was used for the analysis. Results The traditional healers of the study area reported the use of 274 traditional medicinal plant species belonging to 217 genera and 82 families. Asteraceae (11.68%), Fabaceae (9.49%), and Lamiaceae (9.12%) were the foremost frequently used families. Herb species (54.8%) and leaves (65%) were predominantly sourced from the wild environment. The quantity of medicinal plants used (x 2 = 278.368, df = 20, P = 0.000) and years of (experience in) traditional healing using herbs (x 2 = 76.358, df = 10, P = 0.000) varied with distance from the natural forests. The service charge for healing had strong positive association (x 2 = 24.349, df = 5, P = 0.000) with healer's age (x 2 = 309.119, df = 184, P = 0.000) and educational level (x 2 = 851.230, df = 598, P = 0.000) with distance of traditional healer's residence from the medical institution. The agricultural activities, urbanization, low or no charge for the healing service, the secrecy and oral transfer of the knowledge, and the demand for medicinal and other multiple purposes species were some of the factors threatening the resource and the associated knowledge as well as the service in the study area. Conclusion There are diversified traditional medicinal plants applied for healthcare of the community and domestic animals of the study area. The source of remedies mostly depends on herbs of natural forests, and the leaf was the most frequently used plant part. Developing conservation intervention and sustainable systems of utilization is needed for multipurpose medicinal plants. Finally, integrating with modern system and formalizing, legalizing, and capacitating the traditional medicine practitioners are needed for access of primary healthcare systems to rural communities.